Application of Da'wah Bil Hikmah: Efforts to Overcome Radicalism - Yunita, Nurma; Ahmad, Syukraini; Harahap, Rindom; Agustini, Agustini; Sejati, Sugeng; Warsah, Idi (Jurnal Dakwah dan Komunikasi, 2023)
Delivering dakwah that is not in accordance with Islamic teachings and is not as exemplified by Rasulullah SAW, will result in damage both in terms of practice and in terms of understanding of what is received from a preacher. Therefore, it can be said that the radical ideology that has emerged recently is a mistake by a preacher in conveying his preaching. Delivering da'wah can be effective if a da'i can provide comfort to the mad'u or the people being called upon, so that the aim of the da'wah is achieved. The comfort and goals of da'wah can be achieved if a preacher can use da'wah methods well, one of which is the bil hikmah da'wah method. In this article, the method used is the tahlili method or context analysis, namely analyzing the study of the interpretation of the Dakwah bil Hikma verse, thus giving rise to how to apply the Dakwah bil Hikma method as an effort to overcome radical ideologies